Numerical Investigation of the Equalization Enhanced Phase Noise Penalty for M-Quadrature Amplitude Modulation Formats in Short-Haul Few-Mode Fiber Transmission Systems with Time-Domain Equalization - José Manuel Delgado Mendinueta (Applied Sciences, 2018)
The equalization enhanced phase noise (EEPN), caused by the interaction of the chromatic dispersion (CD) with the phase noise of the local oscillator (LO), has been extensively studied for single-mode optical communication systems. Few-mode fiber (FMF) transmission systems introduce a new channel impairment, the differential mode delay (DMD), which also creates EEPN and hence limits the maximum transmission distance of those systems. In this work, we numerically investigate the optical signal to noise ratio (OSNR) penalties caused by the EEPN in a 3-mode FMF transmission system at 25 GBd for quadrature phase-shift keying (QPSK), 16-quadrature amplitude modulation (QAM), 32-QAM and 64-QAM modulation formats when using the blind phase search (BPS) carrier phase recovery (CPR) algorithm, which has been demonstrated to be both robust and suitable for optical communication systems. Our numerical study assumes a short-span of FMF, modeled in the weakly-coupled regime, and includes two cases; the use of ideal mode-selective de/multiplexers at both ends of the FMF span (model A), and the use of ideal non-mode-selective de/multiplexers (model B). The results show that the EEPN has almost no effect in model A. However, EEPN produces a severe penalty in model B with the onset of the OSNR degradation starting for a DMD spread of the impulse response of about 100 symbols for all modulation formats investigated. The distribution ratio of the amount of phase noise between the transmitter and receiver lasers is also assessed for model B and we confirm that the degradation is mainly due to the phase noise of the LO.